2020
DOI: 10.1038/s41467-020-19487-1
|View full text |Cite
|
Sign up to set email alerts
|

A new Majorana platform in an Fe-As bilayer superconductor

Abstract: Iron-chalcogenide superconductors have emerged as a promising Majorana platform for topological quantum computation. By combining topological band and superconductivity in a single material, they provide significant advantage to realize isolated Majorana zero modes. However, iron-chalcogenide superconductors, especially Fe(Te,Se), suffer from strong inhomogeneity which may hamper their practical application. In addition, some iron-pnictide superconductors have been demonstrated to have topological surface stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 35 publications
2
65
0
1
Order By: Relevance
“…These fundamental properties, previously unobserved in superconductors, are consistent with the predications of the theoretical proposal of the QAV 28 . They have broad implications for superconductors with a nontrivial topological band structure and spin-momentum locked superconducting TSS, which have also been found in several other iron-based superconductors such as LiFeAs 35,36 , (Li 0.84 Fe 0.16 )OHFeSe 37 , and CaKFe 4 As 4 38 . We also noticed a recent preprint posted on the arxiv 39 , where the result shows absence of spin-polarization on a ZBP.…”
Section: Discussionmentioning
confidence: 84%
“…These fundamental properties, previously unobserved in superconductors, are consistent with the predications of the theoretical proposal of the QAV 28 . They have broad implications for superconductors with a nontrivial topological band structure and spin-momentum locked superconducting TSS, which have also been found in several other iron-based superconductors such as LiFeAs 35,36 , (Li 0.84 Fe 0.16 )OHFeSe 37 , and CaKFe 4 As 4 38 . We also noticed a recent preprint posted on the arxiv 39 , where the result shows absence of spin-polarization on a ZBP.…”
Section: Discussionmentioning
confidence: 84%
“…Topological band structure has been found to be universal in iron-based superconductors [101]. Vortex MZMs were observed in (Li,Fe)OHFeSe [273,274] and CaKFe 4 As 4 [106]; 4) exploration of new compounds of iron-based superconductors which may support vortex MZM at higher temperatures. Experimental studies identified a topological band structure in a high-T c superconductor Fe(Te,Se) monolayer [267,268], indicating that the monolayer of iron-based superconductor may be a high-temperature Majorana platform above the liquid helium temperature [75].…”
Section: Discussionmentioning
confidence: 99%
“…By implementing the wavefunction and angular momentum analysis, we derived some conclusions of the influence of Dirac surface states on the vortex bound states, as listed below: 1) reversing the direction of magnetic field changes the sign of vorticity, consequently changing the positive and negative correspondence between ν and E ν , but it does not change the sign of the energy of the second solid-circle-pattern level [106]; 2) the sign of the chemical potential determines the sign of the energy of the second solid-circle-pattern level. Specifically, the second solid-circle-pattern level appears in the unoccupied side (positive energy) when µ > 0, and vice versa; 3) at the vortex center, the spin of the zero-energy level is always parallel to the magnetic field, while the spin of the second solid-circle-pattern level is always anti-parallel to the magnetic field.…”
Section: A Vortex Bound State With Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a VUV laser light source with a photon energy range of 5.9-7 eV is utilized in this endstation to improve the ARPES performance. This endstation is open to users and has enabled the discovery of many important materials, such as the bilayer superconductor Fe-As [21], magnetic Weyl semimetal Co 3 Sn 2 S 2 [22], magnetic topological insulator MnBi 2 Te 4 [23][24][25], and topological nodal-line semimetal SrAs 3 [26].…”
Section: Introductionmentioning
confidence: 99%